THE EFFECT OF NEEM GUM ON THE REDUCTION IN RAT BLOOD GLUCOSE LEVELS INDUCED BY STREPTOZOTOCIN - Fardhani, Ichlasul Mahdi; Firdaus, Jauhar; Febianti, Zahrah; Hairrudin, Hairrudin; Abrori, Cholis; Sakinah, Elly Nurus (Buletin Veteriner Udayana, 2023)
Pharmacological therapy for diabetes, which is primarily made up of chemicals, still causes a lot of side effects. The numerous side effects of pharmacological therapy for diabetes have generated innovations in alternative diabetes therapies using ingredients derived from nature. One of the natural ingredients with an anti-hyperglycemia effect is neem gum (NG), or the sap of the neem plant ( Azadirachta indica ). The aim of this study was to determine the effect of NG on the reduction of blood glucose levels. Moreover, this study had six groups, including a normal control group and groups with doses of 0, 3.75, 7.5, 15, and 30 grams/kgBW. The results showed that NG reduced blood glucose levels in diabetic rats. The paired t-test showed a significant reduction in blood glucose in all groups administered NG except for the dose 3.75 group (P<0.05). The minimum and maximum effective doses of NG were calculated using the quadratic regression test with the equation y = 1.059x 2 –46.576x+408. With a target blood glucose level of between 80 and 126 mg/dL, the minimum and maximum effective doses of NG were obtained in the range of 12–15 mg/dL. This study concluded that administering NG to diabetic rats can reduce blood glucose levels. Phytochemical studies and research are needed with serial examinations using the effective dose range of neem gum.